Employed and unemployed job seekers and the business cycle - Simonetta Longhi; Mark Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2013)
The job search literature suggests that on-the-job search reduces the probability of unemployed people finding a job. However, there is little evidence that employed and unemployed job seekers are similar or apply for the same jobs. We compare employed and unemployed job seekers in terms of their individual characteristics, preferences over working hours, job-search strategies and employment histories, and identify how any differences vary over the business cycle. We find systematic differences which persist over the business cycle. Our results are consistent with a segmented labour market in which employed and unemployed job seekers are unlikely to directly compete with each other for jobs.
Keywords: J29; J60; 330; on-the-job search; unemployment; employment histories; panel data